Condom‐use intentions and the influence of partner‐related barriers among women at risk for HIV. Issue 23 (4th March 2013) - Bonacquisti, Alexa; Geller, Pamela A
Abstract : Aims and objectives: To examine intentions to engage in condom use and potential partner‐related barriers to condom use, including intimate partner violence (IPV), low levels of sexual relationship power and perceptions of monogamy, among women at risk for HIV. Background: In the United States, women account for approximately one in four new HIV infections. Despite the effectiveness of consistent condom use, women often confront biological, cultural and psychosocial barriers that limit their ability to engage in condom‐use. Design: Cross‐sectional, quantitative study. Methods: Participants ( N  =   90) were recruited from a domestic violence shelter, a domestic violence support organisation and an obstetrics/gynaecology clinic in Philadelphia, PA. Data were collected by questionnaires to assess women's condom‐use intentions, actual condom‐use behaviour, sexual partner risk factors, experience of IPV, level of sexual relationship power and perceptions of monogamy. Results: Fifty‐eight per cent of participants ( n  =   52) indicated a difference between their preference and intentions to use condoms vs. their actual use, with 62% ( n  =   32) using condoms less frequently than they would like. Significant differences in condom use emerged for women with low vs. high sexual relationship power and women who reported being in a monogamous relationship vs. those who did not. Of particular concern, a majority of these relationships were with high‐risk partners, further increasing women's already elevated risk of acquiring HIV. Conclusions: Condom use is a multifaceted issue, particularly in sexual relationships involving power differentials and perceived monogamy. Condom use was complicated by women's own preferences, sexual relationship power differentials and by the perceived exclusivity of the relationship with their sexual partners. Relevance to Clinical Practice: These findings have important implications for nurses as they are uniquely positioned to facilitate HIV risk reduction among their patients through the discussion of sexual health issues and barriers to negotiating condom use that women may confront.